Transmission of Domestic and External Shocks through Input-Output Network : Evidence from Korean Industries - Lee, Dongyeol (IMF Working Papers; Working Paper ;, 2019)
In the last two decades, manufacturing industries in Korea have become more concentrated, and interconnectedness across industries and to foreign countries has risen via vertical relationships and trade linkages. This paper investigates the transmission of economic shocks in such a highly concentrated and interconnected structure, focusing on the role of vertical and trade linkages and using the industry-level international input-output data. The results suggest that, first, the role of vertical and trade linkages in propagating growth shocks from both domestic sources and external sources is important. Second, the growth impact of a few key sources of economic shocks is relatively large. These findings highlight that economic shocks in a few key industries and/or major trading partners that are transmitted through vertical and trade linkages can lead to large swings in the overall economy. This paper contributes to the understanding of the potential interactions between the industrial structure and economic growth and stability.